A Qualitative Exploration of the Economic and Social Effects of Microcredit among People Living with HIV/AIDS in Uganda - Glenn Wagner; Yashodhara Rana; Sebastian Linnemayr; James Balya; Lydia Buzaalirwa (AIDS Research and Treatment)
HIV medical care, including antiretroviral therapy (ART), is often successful in restoring physical health and functioning. But in developing countries, HIV medical care is often insufficient to achieve social and economic health, and hence innovative economic support programs are much needed. We conducted semistructured interviews with 30 adults receiving ART and microcredit loans operated by Uganda Cares. Using content analysis, we explored the impact of the microcredit loans on the economic, social, and psychological well-being of respondents. Most respondents indicated that the microcredit loans played a positive role in their lives, helped them to keep their children in school and sustain their families, and improved their self-esteem and status in the community. In addition, we also found significant positive knowledge spill-over and network effects in the program with regard to business management and support. However, more than half of the participants indicated experiencing repayment problems either personally or with other group members due to unexpected emergencies and sickness. These findings highlight that microcredit programs have the potential of being an economic support system for HIV clients trying to reestablish their livelihoods, especially in resource-constrained settings, though more research is needed to determine the overall economic viability of such programs.